Antibacterial Activity of Syzygium aromaticum (Clove) Bud Oil and Its Interaction with Imipenem in Controlling Wound Infections in Rats Caused by Methicillin-Resistant Staphylococcus aureus - Abdulaziz Khaleef Alanazi; Mohammed Hussein Alqasmi; Mohammed Alrouji; Fahd A. Kuriri; Yasir Almuhanna; Babu Joseph; Mohammed Asad (Molecules, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the leading causes of infection worldwide. Clove oil’s ability to inhibit the growth of MRSA was studied through in vitro and in vivo studies. The phytochemical components of clove oil were determined through gas chromatography-mass spectrometry (GC-MS) analysis. The antibacterial effects of clove oil and its interaction with imipenem were determined by studying MIC, MBC, and FIC indices in vitro. The in vivo wound-healing effect of the clove oil and infection control were determined using excision wound model rats. The GC-MS analysis of clove oil revealed the presence of 16 volatile compounds. Clove oil showed a good antibacterial effect in vitro but no interaction was observed with imipenem. Clove bud oil alone or in combination with imipenem healed wounds faster and reduced the microbial load in wounds. The findings of this study confirmed the antibacterial activity of clove oil in vitro and in vivo and demonstrated its interaction with imipenem.